Pendekatan Psikologi Positif (Emotional Intelligence) untuk Menciptakan Lingkungan Sekolah Dasar Bebas Bullying - Indryani Sapta Wulandari; Sischa Wahyuwardhani; Novi Widya Sari; Yogi Rahmadhani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Cases of bullying in the world of education, especially at the elementary school level, are increasing and becoming a serious concern. This research aims to develop an understanding of bullying in elementary school students through a positive psychology approach, especially in the aspect of emotional intelligence. This study uses an experimental quantitative method with a pre-experimental design and One Group Pre-test–Post-test Design. The sample of this study is 18 MI Miftahul Huda students, who were selected using a simple random sampling technique. The intervention provided involves psychoeducation with lecture and role play methods to improve understanding of bullying, which is measured by emotional intelligence-based knowledge instruments. Data analysis was carried out using the Wilcoxon Test with the help of SPSS. The results of the research are expected to contribute to the prevention of bullying in elementary schools by increasing student awareness and empathy.